A quantitative analysis of the quality and content of the health advice in popular Australian magazines - Amanda Wilson; David Smith; Roseanne Peel; Jane Robertson; Kypros Kypri (Elsevier, 2017)
Abstract Objective: To examine how health advice is provided in popular magazines and the quality of that advice. Methods: A prospective quantitative analysis of the quality of health advice provided in Australian magazines between July and December 2011 was conducted. A rating instrument was adapted from the Media Doctor Australia rating tool used to assess quality of health news reporting. Criteria included: recommends seeing a doctor; advice based on reliable evidence; advice clear and easily applied; benefits presented meaningfully; potential harms mentioned; evidence of disease mongering; availability and cost of treatments; obvious advertising; vested interest, and anecdotal evidence. Results: 163 health advice articles were rated showing a wide variation in the quality of advice presented between magazines. Magazines with 'health' in the title, rated most poorly with only 36% (26/73) of these articles presenting clear and meaningful advice and 52% (38/73) giving advice based on reliable evidence. Conclusions: Australian magazines, especially those with health in the title, generally presented poor quality, unreliable health advice. Teen magazine Dolly provided the highest quality advice. Implications: Consumers need to be aware of this when making health choices.